Autoevaluación de los estudiantes en la práctica profesional de la Licenciatura en Nutrición, 2019 - Ravelli, Sandra (Universidad Nacional del Litoral, 2022)
In the professional practice of the Bachelor of Nutrition, the student assumes a commitment to the curricular space and to the assigned places of practice, experiencing training instances in pursuit of their professional training. In that order, it is possible to give the student joint responsibility in the decision-making process that the evaluation involves. To implement the self-evaluation process of the students of the professional practice of the Bachelor of Nutrition in the three areas experienced, in the 2019 cohort. A sample of 33 students was studied. A questionnaire was used, developed within the framework of an extracurricular training activity in research and development. The students valued the process, prioritizing attitudinal aspects. Adapting to different situations is the most weighted competition. The link with the tutor and training environments that promote autonomy in the development of future professionals are revalued. Through this contribution, it is intended to review the subject, its methodology and to know transversal and disciplinary competences developed by the students.